PENGARUH SARANA PRASARANA TERHADAP KEJENUHAN BELAJAR SERTA IMPLIKASINYA PADA HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN EKONOMI (Survei Pada Peserta Didik Kelas X, XI dan XII SMA Nangtang Kabupaten Tasikmalaya Tahun Ajaran 2023/2024) - Dewi Purwanti; Yoni Hermawan; Gugum Gumilar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research is motivated by the problem of low student learning outcomes in economics subjects. This study aims to determine the influence of school infrastructure on learning saturation and its implications on the learning outcomes of students of economics subjects in grades X, XI and XII of IPS Nangtang High School, Tasikmalaya Regency for the 2023/2024 school year. In this study, a survey research method was used with a quantitative approach, through an explanatory design. Data collection techniques use questionnaires and documentation and data analysis techniques use the help of the SPSS program. The population in this study is 91 students, using a saturated sampling technique. The results of the study showed that: there was an influence between infrastructure facilities on learning saturation, infrastructure variables on learning outcomes, learning saturation variables on learning outcomes and the influence between infrastructure variables on learning outcomes through learning saturation. The contribution of the direct influence of the infrastructure variable (X) on learning outcomes (Y) was 22% while the contribution of the indirect influence of the infrastructure variable (X) on learning outcomes (Y) through learning saturation (Z) was 64.3%. So that the amount of indirect influence is greater than the direct influence.